2020
DOI: 10.20944/preprints202007.0234.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microwave Extraction vs. Other Techniques for Industrial Scale Cannabis Extraction

Abstract: Cannabis is a flowering plant that has long been used for medicinal, therapeutic, and recreational purposes. Cannabis contains more than 500 different compounds, including a unique class of terpeno-phenolic compounds known as cannabinoids; Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are the most prevalent cannabinoids and have been associated with the therapeutic and medicinal properties of the cannabis plant. In this paper, continuous flow microwave assisted extraction (MAE) is presented and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Microwave-assisted extraction is reported as a sustainable method because of the use of less energy with quick processing and less solvent consumption (Uzel & Uzel, 2018). However, the final product from the extraction contains target compounds in high purity and high yield (Radoiu et al, 2020). de Vita et al (2019) compared different methods for cannabinoids by investigating the temperature, solvent and time and found that increase in temperature and time caused 4 times higher than the extraction methods using ethanol at 90 °C for 15 min.…”
Section: Sustainability Aspects Of the Extraction Methodsmentioning
confidence: 99%
“…Microwave-assisted extraction is reported as a sustainable method because of the use of less energy with quick processing and less solvent consumption (Uzel & Uzel, 2018). However, the final product from the extraction contains target compounds in high purity and high yield (Radoiu et al, 2020). de Vita et al (2019) compared different methods for cannabinoids by investigating the temperature, solvent and time and found that increase in temperature and time caused 4 times higher than the extraction methods using ethanol at 90 °C for 15 min.…”
Section: Sustainability Aspects Of the Extraction Methodsmentioning
confidence: 99%